Potential directions for improving production processes in Industry 4.0 conditions based on a Polish furniture enterprise – a case study - Jasińska, Katarzyna; Szala, Łukasz (Potencjalne kierunki doskonalenia procesów produkcji w warunkach Industry 4.0 na przykładzie polskiego przedsiębiorstwa meblarskiego – case study, 2021)
The aim of the article is to outline potential directions of changes in production processes in furniture manufacturing that may occur under the impact of Industry 4.0. The research methods used as part of the study include a critical literature review, nd a case study of a selected company operating in the furniture manufacturing sector supplemented with a survey. The results obtained indicate the impact of Industry 4.0 on enterprises operating in this sector, which is visible in their efforts aimed at modernizing their production processes. A particularly important direction of the changes involves the implementation of integrated systems, processing data in real time, which allows for customizing the manufacturing while meeting the requirements of mass production. The results obtained broaden the knowledge of the application of 4.0 technologies in areas that involve the use of simple technologies, including industries with low levels of innovation, i.e. in sectors traditionally not susceptible to revolutionary changes brought about by new production management technologies.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 2 (60), s. 27-46
Keywords: production process; process improvement; Industry 4.0; furniture sector; procesy produkcyjne; doskonalenie procesów; sektor meblarski